Simultaneous velocity measurements and the coupling effect of the liquid and gas phases in slug flow using PIVâLIF technique - Siddiqui, M.I. (Springer Verlag, 2016)
Abstract: The analysis of a two-phase slug flow is of immense importance due to its vast applications in many industrial problems. A number of experimental and analytical studies have been carried out to study this complex and unwanted phenomenon. Mostly, these studies were limited to the liquid phase and to the statistical parameters and formation mechanism. So far, no attempt has been made to study the phase interaction and coupling effects of both phases simultaneously, which is more important in understanding this complex flow behavior. This kind of study requires the instantaneous velocity fields of both phases simultaneously. Therefore, in this study a PIVâLIF technique has been applied to study two-phase (liquidâgas) slug flow in a laboratory facility. Water and gas were considered as working fluids, and slug flow was generated in a nearly horizontal pipe with an inclination of 1.16Â° to consider the terrain slugging mechanism. Liquid and gas phases were seeded simultaneously with fluorescent and titanium dioxide tracer particles, respectively. Two CCD cameras installed with low pass and band pass filters were used to capture images for separate phases. Instantaneous velocity field for both liquid and gas phases was measured simultaneously. To extract the coherent structures and for the analysis of turbulence in liquid and gas phase, the proper orthogonal decomposition (POD) analysis technique was applied to the velocity fields. Large energyÂ containing modes were successfully revealed by POD. The energy distribution of spatial modes for both phases was also measured and compared. Graphical abstract: Figure not available: see fulltext. Â© 2015, The Visualization Society of Japan.